2002
DOI: 10.1002/1099-0682(200203)2002:3<629::aid-ejic629>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Ring Closure Kinetics of Bidentate Hemilabile P,N and P,S Ligands on a Platinum(II) Complex

Abstract: Complexes of the type cis-[PtPh 2 (CO)(η 1 -P−N)] and cis-[PtPh 2 (CO)(η 1 -P−S)], where bidentate phosphorus−nitrogen and phosphorus−sulfur ligands are bound to the metal centre in a monodentate fashion [P−N = Ph 2 PC 5 H 4 N (Ph 2 PPy), Ph 2 P(CH 2 ) 2 C 5 H 4 N (ppye), Ph 2 P(o-C 6 H 4 )NMe 2 (PNMe 2 ), Ph 2 P(CH 2 ) n NMe 2 (n = 2, 3, i.e., peNMe 2 and ppNMe 2 ) and P−S = Ph 2 P(CH 2 ) 2 SEt (P−SEt), Ph 2 P(CH 2 ) n SPh (n = 1, 2, i.e., P−CH 2 SPh and P−SPh)], were prepared in situ by reaction of the hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 111 publications
4
26
0
Order By: Relevance
“…The substitution reactions of the homoditopic S–S ligands of [Pt(Ph) 2 {κ 2 ‐( S , S )‐Ph 2 S(CH 2 ) n SPh 2 }] ( n = 2,3) by a diphosphane were found to proceed according to Equation (2), indicating the formation of a monodentate κ 1 ‐ S transient species 36. Parallel first‐ and second‐order kinetics were also observed for the acid‐promoted ring openingand displacement by chloride of the bidentate chelateligand from dichloro[pyridine‐2‐(α‐methoxymethanolato)]gold(III) 14d…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…The substitution reactions of the homoditopic S–S ligands of [Pt(Ph) 2 {κ 2 ‐( S , S )‐Ph 2 S(CH 2 ) n SPh 2 }] ( n = 2,3) by a diphosphane were found to proceed according to Equation (2), indicating the formation of a monodentate κ 1 ‐ S transient species 36. Parallel first‐ and second‐order kinetics were also observed for the acid‐promoted ring openingand displacement by chloride of the bidentate chelateligand from dichloro[pyridine‐2‐(α‐methoxymethanolato)]gold(III) 14d…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…It can be expected that the methoxy phosphane resembles the thiomethoxy phosphane and thus assume that aminophosphane is also more basic than thiomethoxy phosphane. Recent studies on ring closure kinetics of bidentate hemilabile (np) and (sp) ligands on platinum [42] showed that the ring closure rate constant is faster than the rate constant for the opening, suggesting that the equilibrium between chelated and non-chelated complexes is shifted towards the chelated species. This means that once the ring is formed (fast rate) cleavage of the metal-nitrogen or metal-sulphur bond is difficult (slow rate).…”
Section: Chelated Complexesmentioning
confidence: 99%
“…6a or 9 ), together with the final chelated species and free dimethyl sulfoxide (diagnostic signal at 2.5 ppm). Any attempts to identify by 1 H NMR spectroscopy, even at low temperatures, the presence of other intermediate open‐ring species or, in the case of the trans ‐platinum(II) complex Pt2 , other coordination isomers were unsuccessful 20. This means that the kinetic rate constant for the sulfoxide ring‐closure is too high compared with that of the substitution process of the pyridine moiety, leading to the conclusions that the open‐ring species once formed is rapidly converted into the corresponding chelated species 20,21.…”
Section: Resultsmentioning
confidence: 99%
“…Platinum(II) Complexes Derivatives: The platinum(II) compounds cis ‐[PtMe 2 (Me 2 SO) 2 ] ( Pt1 )19 and trans ‐[PtMeCl(Me 2 SO) 2 ] ( Pt2 )20 were prepared according to already published methods and were purified by several crystallizations from a 1:1 CH 2 Cl 2 /Et 2 O mixture (v/v).…”
Section: Methodsmentioning
confidence: 99%